ANALISA EKSPERIMENTAL MODULUS ELASTISITAS BAHAN KOMPOSIT GLASS FIBER REINFORCED PLASTIC (GFRP) BERDASARKAN VARIASI DIAMETER SERAT AKIBAT BEBAN IMPAK LAJU REGANGAN TINGGI - Achmad Jusuf Zulfikar (Universitas Medan Area, 2017)
GFRP composite is one of the alternative materials that the most common as a replacement for metal. This material has a light weight, easy to shape, good strength, and the production cost is relatively cheaper. This study aims to investigate the effects of fiber diameter variation of mechanical behavior, particularly on the load of high strain rate impact. The application of impulse momentum theory in the elastic region is the basic science for this case. The AGC apparatus is equipment that used for this test because it could generate the high strain wave rate in the single direction loading. Specimen is placed in the position of tight end against the end of the input bar. The results showed that the increase in fiber diameter variations affect the value of E that is produced. Thus, it is become a recommendation for the use of this material in certain circumstances.